Dividend payout policy and financial crisis: Evidence from the life cycle theory - Rehana Kouser; Rabia Luqman; Asif Yaseen; Muhammad Azeem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Study aims to check the impact of financial crisis on the dividend payout policy by using the life cycle variables. To check this relationship, logit model is used to predict the probability to pay the dividend. Sample selected of 285 companies of non-financial sector listed at KSE by using the method of Fama and French (2001). Panel data is used to check this relationship for the period of 2001 to 2011. Results are analyzed through SSPS which shows that dividend has been changed significantly during the crisis. This research has shown that firms tend to maintain the high liquidity in the time of crisis.
Keywords: 330; Dividends; Dividend policy; Recession; Financial crisis; Life-cycle model